Exploring learner interest in relation to humanistic language teaching materials: A case from Vietnam. (April 2022) - Pham, Luan Nhu; Tin, Tan Bee
Abstract: The study investigated the construct of learner interest in relation to humanistic activities, compared to textbook activities used in the EFL classroom. It explored the affective experiences the learners had, the value they perceived of the language activities, and the knowledge-seeking (learning) behaviours they performed in relation to the two types of materials. Two small classes of students participated in a mixed-methods QUANqual design experiment. Five activities were selected from popular EFL global textbooks and five comparable humanistic activities were developed. These two types of materials were applied in an alternating and counterbalanced manner within and between classes. The findings show that the learners experienced more diverse and positive emotions and performed more positive learning behaviours during humanistic activities compared to textbook activities. The study indicates that not only uninteresting materials but also already-interesting materials can be effectively humanised to be more interesting to learners. Implications related to the manipulation of teaching materials to promote learners' interest are also discussed.